The Role Of The Counseling Teacher In Developing The Value Of Ta'awun (Mutual Help) Inclusive Education Institutions - Beni Azwar; Sakinah Soleh; Fadilah Fadilah (POTENSIA: Jurnal Kependidikan Islam, 2022)
This interview study reports on the experience of 7 Guidance and Counseling teachers developing the value of helping inclusive madrasah students in West Sumatra, Indonesia. Data was collected employing semi-structured interviews to explore the experience of the counseling teacher. Data were analyzed by thematic content analysis. The results of the study show two general findings, namely that Guidance and Counseling teachers play a role in fostering an attitude of helping students in inclusive education institutions through orientation services and individual counseling. Besides that, Guidance and Counseling teachers collaborate with religious teachers in charity activities such "As Sedeqah Fridays which are collected from both ordinary students and special needs children. This study emphasizes the importance of Guidance and Counseling teachers receiving technical training in educating children with special needs.